Minimum Inhibitory Concentration (MIC) and the Non-Inhibitory Concentration (NIC) values of Salvia officinalis methanolic extract against Aeromonas hydrophila - Ismail, Ahmad Syazwan; Shukor, Mohd Yunus; Masdor, Noor Azlina (Hibiscus Publisher, 2022)
Extractions from plants have been the subject of considerable research because of their potential to inhibit the growth of bacteria. It was not possible to compare the outcomes of this study to those of previous investigations because these discoveries were not reported on in the benchmark values. The use of data-driven nonlinear regression analysis as one of the approaches to finding this value is among the approaches with the highest degree of precision. Using Lambert and Pearson's modified Gompertz model, it was possible to successfully determine the minimum inhibitory concentration (MIC) and the non-inhibitory concentration (NIC) of the methanolic extract of Salvia officinalis (sage) against the pathogen Aeromonas hydrophila. Sage's MIC and NIC values, which come in at 31.92 (95% Confidence Interval from 29.85 to 34.28) and 15.56 mg/mL (95% C.I. from14.39 to 16.71), respectively, suggest that it has the potential to be utilized as an inhibitory drug against this critical fish pathogen. This is demonstrated by the model's strong correlation coefficient, which was 0.995.